Factores de riesgo asociados a ruptura prematura de membranas en gestantes de 20 a 35 años en el Hospital General Martín Icaza, babahoyo, octubre 2024 – mayo 2025. - Herrera Winso, Kerly Dayana (2025)
Premature rupture of membranes (PROM) is a significant obstetric complication that can generate significant risks for maternal and neonatal health, such as intra-amniotic infections, preterm birth, and neonatal morbidity. This study aims to identify risk factors associated with PROM in pregnant women aged 20 to 35 years treated at the Martín Icaza General Hospital, Babahoyo, Ecuador throughout 2024. Sociodemographic, clinical, and obstetric variables will be evaluated to determine their correlation with the incidence of PROM. A cross-sectional, observational, and analytical approach will be used, collecting data from clinical records and structured interviews with patients. Descriptive and inferential statistical methods will be applied to analyze the relationships between risk factors such as age, obstetric history, infections, and prenatal care. In addition, compliance with clinical protocols in the management of PROM and its impact on maternal-neonatal outcomes will be evaluated. The results will provide valuable information on the prevalence of PROM and the factors that influence its occurrence, offering a basis for the development of preventive strategies, the improvement of prenatal care and the optimization of clinical protocols. The conclusions will emphasize the importance of early detection, adequate prenatal care and timely interventions to reduce the incidence of PROM and its related complications. This research will contribute to improving obstetric care, maternal-neonatal outcomes and informing policies aimed at reducing morbidity and mortality associated with PROM in the region.